Multishot Codes for Network Coding Using Rank-Metric Codes - Nóbrega, Roberto W; Uchôa-Filho, Bartolomeu F (2010 IEEE Wireless Network Coding Conference, 2010)
The multiplicative-additive finite-field matrix channel arises as an adequate model for linear network coding systems when links are subject to errors and erasures, and both the network topology and the network code are unknown. In a previous work we proposed a general construction of multishot codes for this channel based on the multilevel coding theory. Herein we apply this construction to the rank-metric space, obtaining multishot rank-metric codes which, by lifting, can be converted to codes for the aforementioned channel. We also adapt well-known encoding and decoding algorithms to the considered situation.